Jambul Barber: haircut services / Mohammad Ismail Talib, Muhammad Al-Abrar Zamri & Nayli Aqilah Mohamad Azman - Talib, Mohammad Ismail; Zamri, Muhammad Al-Abrar; Mohamad Azman, Nayli Aqilah (2017)
We also use and sell a range of skin moisturizers, wrinkles cream and body oils which are free from animal testing, organically produced and environmentally safe. Our barbers will style one's hair, and a stylist will provide a relaxing shampoo and cooling conditioner. Standard features include a hot soothing towel, trim mustaches and each customer gets and old fashion barber massage. Our equipment includes the latest hairdressing chairs and equipment, seats and recliners. While one waits we offer the latest newspapers and magazines or enjoy watching flat screen TV. We can do any modem or traditional hair style available today. From flattops, spikes, blowouts, and brooks to regulars. And always include a hot lather neck shave for men and relaxing shoulder massage after each service. Flat screens monitors are placed at various intervals in the barber shop with databases containing information about hairstyles, skin types and products and their uses.